Phospholane-Catalyzed Wittig Reaction - Werner, Thomas; Hoffmann, Marcel; Deshmukh, Sunetra (European Journal of Organic Chemistry)
Keywords: Organic Chemistry; Physical and Theoretical Chemistry

Synthesis of Cyclic Carbonates from Epoxides and Carbon Dioxide by Using Bifunctional One-Component Phosphorus-Based Organocatalysts - Büttner, Hendrik; Steinbauer, Johannes; Werner, Thomas (ChemSusChem)
Keywords: General Energy; General Materials Science; General Chemical Engineering; Environmental Chemistry

First Base-Free Catalytic Wittig Reaction - Schirmer, Marie-Luis; Adomeit, Sven; Werner, Thomas (Organic Letters)
Keywords: Organic Chemistry; Physical and Theoretical Chemistry; Biochemistry

Crystal structure of diethyl (E)-2-[(benzofuran-2-yl)methylidene]succinate - Schirmer, Marie-Luis; Spannenberg, Anke; Werner, Thomas (Acta Crystallographica Section E Crystallographic Communications)
The title compound, C 17 H 18 O 5 , was synthesized by a base-free catalytic Wittig reaction. The molecule consists of a diethyl itaconate unit, which is connected via the C=C double bond to a benzofuran moiety. The benzofuran ring system (r.m.s. deviation = 0.007 Å) forms dihedral angles of 79.58 (4) and 12.12 (10)° with the mean planes through the cis and trans ethoxycarbonyl groups, respectively. An intramolecular C—H...O hydrogen bond involving the O atom of the benzofuran moiety is observed. In the crystal, molecules are linked into ribbons running parallel to the b axis by C—H...O hydrogen bonds.
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Highly Efficient Polymer-Supported Catalytic System for the Valorization of Carbon Dioxide - Desens, Willi; Kohrt, Christina; Frank, Marcus; Werner, Thomas (ChemSusChem)
Keywords: General Energy; General Materials Science; General Chemical Engineering; Environmental Chemistry

Organocatalyzed Reduction of Tertiary Phosphine Oxides - Schirmer, Marie-Luis; Jopp, Stefan; Holz, Jens; Spannenberg, Anke; Werner, Thomas (Advanced Synthesis and Catalysis)
Keywords: General Chemistry

Dual-based adaptive FEM for inelastic problems with standard FE implementations - Widany, K.-U.; Mahnken, Rolf (International Journal for Numerical Methods in Engineering)

Adaptive FEM with goal-oriented error estimation and an approximation of the dual problem for inelastic problems - Widany, Kai-Uwe; Mahnken, Rolf (PAMM)

Uncertainty quantification for linear elastic bodies with two fluctuating input parameters - Dridger, Alex; Caylak, Ismail; Mahnken, Rolf (PAMM)

A coupled phase-field - Cahn-Hilliard model for lower bainitic transformation - Düsing, Martin; Mahnken, Rolf (PAMM)

Transition from hyperelastic micromorphic to micropolar and microstrain continua - Leismann, Thorben; Mahnken, Rolf (PAMM)

Non-linear Stochastic Finite Element - Caylak, Ismail; Dridger, Alex; Mahnken, Rolf (PAMM)

Evaluation of different approaches for modeling phase transformations in machining simulation - Schulze, Volker; Uhlmann, Eckart; Mahnken, Rolf; Menzel, Andreas; Biermann, Dirk; Zabel, Andreas; Bollig, Patrick; Ivanov, Ivan M.; Cheng, Chun; Holtermann, Raphael; Bartel, Thorsten (Production Engineering)

A Novel Finite Element Approach to Modeling Hard Turning in Due Consideration of the Viscoplastic Asymmetry Effect - Uhlmann, Eckart; Mahnken, Rolf; Ivanov, Ivan Mitkov; Cheng, Chun (Procedia CIRP)

Simulation of lower bainitic transformation with the phase-field method considering carbide formation - Düsing, M.; Mahnken, Rolf (Computational Materials Science)

Parameter identification for rubber materials with artificial spatially distributed data - Nörenberg, Nicole; Mahnken, Rolf (Computational Mechanics)

Chemically and thermally stable, emissive carbon dots as viable alternatives to semiconductor quantum dots for emissive nematic liquid crystal–nanoparticle mixtures with lower threshold voltage - Urbanski, Martin; Mirzaei, Javad; Sharma, Anshul; Hofmann, Daniel; Kitzerow, Heinz-Siegfried; Hegmann, Torsten (Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Electrically tunable zero dispersion wavelengths in photonic crystal fibers filled with a dual frequency addressable liquid crystal - Wahle, Markus; Kitzerow, Heinz-Siegfried (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

A Central Limit Theorem for Random Walks on the Dual of a Compact Grassmannian - Rösler, Margit; Voit, Michael (Symmetry, Integrability and Geometry: Methods and Applications)
Keywords: Geometry and Topology; Mathematical Physics; Analysis

Von der Flüchtigkeit der Begehrens oder Ménage-à-trois in Francois Truffauts Jules et Jim, Stanley Kubricks Eyes wide shut und Tom Tykwers Drei - Morrien, Rita (Sprachen der Liebe in Literatur, Film und Musik. Von Platons Symposion bis zu zeitgenössischen Serien)

Broken Heroes. Die (Un-)Ordnung der Geschlechter im populären Film - Morrien, Rita (Außerschulische Bildung. Zeitschrift der politischen Jugend- und Erwachsenenbildung)

Antiautoritäre Erziehung - Bock, Karin; Göddertz, Nina; Heyden, Franziska; Mauritz, Miriam (Lexikon Kindheitspädagogik)

Kinderladen - Bock, Karin; Göddertz, Nina; Heyden, Franziska; Mauritz, Miriam (Lexikon Kindheitspädagogik)

Feedback zu Leseprozessen und wahrgenommenes Klassenklima aus der Sicht von Grundschulkindern im dritten und vierten Schuljahr. Vortrag auf der 3. Tagung der Gesellschaft für Empirische Bildungsforschung (GEBF) - Hoya, Fabian Karl; Hellmich, Frank

Prädiktoren für Einstellungen von Lehrerinnen und Lehrern zur Inklusion in der Grundschule. Vortrag auf der 3. Tagung der Gesellschaft für Empirische Bildungsforschung (GEBF) - Görel, Gamze; Hellmich, Frank

Rückmeldungen zu Leseprozessen in Elternhaus und Schule aus der Sicht von Kindern im Grundschulalter und ihre Bedeutung für die Lesemotivation. Vortrag auf der Jahrestagung der Sektion Schulpädagogik der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE) - Hoya, Fabian Karl; Hellmich, Frank

Einstellungen und Motivation von Studentinnen und Studenten des Lehramts an Grundschulen in Bezug auf inklusiven Unterricht. Vortrag auf der Jahrestagung der Sektion Schulpädagogik der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE) - Görel, Gamze; Ort, Margarita; Hellmich, Frank

Inklusion als Herausforderung in Schule und Unterricht. Vortrag im Rahmen des Kolloquiums „Inklusion als Herausforderung im Bildungswesen – Beiträge aus der empirischen Bildungsforschung zum inklusiven Lernen“ - Hellmich, Frank; Albers, Timm; Ritter, Eva Charlotte; Görel, Gamze; Pfahl, Rebecca

Kosten und Nutzen Früher Hilfen – aktuelle Erkenntnisse und zukünftiger Forschungsbedarf - Wagenknecht, Inga; Meier-Gräwe, Uta; Ziegenhain, Ute (Interdisziplinäre Fachzeitschrift der DGfPl)

Stefan Mähl: Mehrgliedrige Verbalkomplexe im Mittelniederdeutschen. Ein Beitrag zu einer historischen Syntax des Deutschen (Niederdeutsche Studien 57), Köln, Weimar, Wien 2014. - Wallmeier, Nadine (Rheinische Vierteljahresblätter)

Giant narrowband twin-beam generation along the pump-energy propagation direction - Pérez, Angela M.; Spasibko, Kirill Yu; Sharapova, Polina; Tikhonova, Olga V.; Leuchs, Gerd; Chekhova, Maria V. (Nature Communications)
Abstract Walk-off effects, originating from the difference between the group and phase velocities, limit the efficiency of nonlinear optical interactions. While transverse walk-off can be eliminated by proper medium engineering, longitudinal walk-off is harder to avoid. In particular, ultrafast twin-beam generation via pulsed parametric down-conversion and four-wave mixing is only possible in short crystals or fibres. Here we show that in high-gain parametric down-conversion, one can overcome the destructive role of both effects and even turn them into useful tools for shaping the emission. In our experiment, one of the twin beams is emitted along the pump Poynting vector or its group velocity matches that of the pump. The result is markedly enhanced generation of both twin beams, with the simultaneous narrowing of angular and frequency spectrum. The effect will enable efficient generation of ultrafast twin photons and beams in cavities, waveguides and whispering-gallery mode resonators.
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

Projective filtering of the fundamental eigenmode from spatially multimode radiation - Pérez, A. M.; Sharapova, Polina; Straupe, S. S.; Miatto, F. M.; Tikhonova, O. V.; Leuchs, G.; Chekhova, M. V. (Physical Review A)
Keywords: Atomic and Molecular Physics; and Optics

Direct Schmidt number measurement of high-gain parametric down conversion - Dyakonov, I V; Sharapova, Polina; Iskhakov, T Sh; Leuchs, G (Laser Physics Letters)
Keywords: Physics and Astronomy (miscellaneous); Instrumentation

Schmidt modes in the angular spectrum of bright squeezed vacuum - Sharapova, Polina; Pérez, A. M.; Tikhonova, O. V.; Chekhova, M. V. (Physical Review A)
Keywords: Atomic and Molecular Physics; and Optics

Lehr-Lernkonzepte für den inklusiven Unterricht in der Grundschule. Vortrag und Workshop auf dem Paderborner Grundschultag 2015 - Hellmich, Frank; Blumberg, Eva

Gemeinsames Lernen im naturwissenschaftlich-technischen Sachunterricht. Vortrag und Workshop auf dem Paderborner Grundschultag 2015 - Blumberg, Eva; Hellmich, Frank

Phosphorus-doped carbon–carbon nanotube hierarchical monoliths as true three-dimensional electrodes in supercapacitor cells - Patiño, Julián; Lopez Salas, Nieves; Gutiérrez, María C.; Carriazo, Daniel; Ferrer, M. Luisa; Monte, Francisco del (Journal of Materials Chemistry A)
Phosphorus-doped carbon–carbon nanotube hierarchical monoliths exhibiting energy densities of around 22.6 W h kg−1 at power densities of up to 10 kW kg−1 were capable of functioning as true three-dimensional electrodes in supercapacitor cells.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Nitrogen-doped carbons prepared from eutectic mixtures as metal-free oxygen reduction catalysts - Lopez Salas, Nieves; Gutiérrez, María C.; Ania, Conchi O.; Muñoz-Márquez, Miguel A.; Luisa Ferrer, M.; Monte, Francisco del (Journal of Materials Chemistry A)
Deep eutectic solvents (DESs) composed of resorcinol, either 2-cyanophenol or 4-cyanophenol, and choline chloride were used for the synthesis of hierarchical nitrogen-doped carbon molecular sieves.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

"Ich habe einen anderen Blick auf die Arbeit und die Kinder" - Ergebnisse der Absolvenetnbefragung des Bielefelder Studiengangs "Integrierte Sonderpädagogik" - Kottmann, Brigitte; Hofauer, Friederike (Herausforderung Inklusion. Theoriebildung und Praxis)

Localization of coherent signals without source number knowledge in unknown spatially correlated Gaussian noise - Qian, C.; Huang, L.; Xiao, Y-.H.; So, H. C. (Signal Processing)

Two-step reliability test based unitary root-MUSIC for direction-of-arrival estimation - Qian, C.; Huang, L.; Xiao, Y-.H.; So, H. C. (Digital Signal Processing)

Flag Manifolds for the Characterization of Geometric Structure in Large Data Sets - Marrinan, Tim; Beveridge, J. Ross; Draper, Bruce; Kirby, Michael; Peterson, Chris (Numerical Mathematics and Advanced Applications-ENUMATH 2013)

Asymptotic parameter tracking performance with measurement data of 1-bit resolution - Stein, Manuel; Kürzl, Alexander; Mezghani, Amine; Nossek, Josef A. (IEEE Trans.\ Signal\ Process.)

Experimental evaluation of interference alignment for broadband WLAN systems - Lameiro, Christian; García-Naya, Jose A.; Santamaría, Ignacio; Castedo, Luis (EURASIP Journal on Wireless Communications and Networking)

Performance Analysis of Volume-based Spectrum Sensing for Cognitive Radio - Huang, L.; Qian, C.; Xiao, Y-.H.; Zhang, Q. T. (IEEE Transactions on Wireless Communications)

Robust Spectrum Sensing for Noncircular Signal in Multiantenna Cognitive Receivers - Huang, L.; Xiao, Y-.H.; Zhang, Q. T. (IEEE Transactions on Signal Processing)

A simple DoF-achievable scheme for the Gaussian interference channel with delayed CSIT - Rezaee, M.; Schreier, P. J.; Guillaud, M.; Clerckx, B. (Proc. IEEE Global Communications Convference: Communication Theory)

Signal parameter estimation performance under a sampling rate constraint - Lenz, Andreas; Stein, Manuel; Nossek, Josef A. (Asilomar Conf.\ Signals Syst.\ Computers)

Arendt, Hannah - Alpsancar, Suzana (Flusseriana)

Work/Arbeit/Trabalho - Alpsancar, Suzana (Flusseriana)